2020
DOI: 10.3390/ijns6020026
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dried Blood Spot Specimens to Monitor Patients with Inherited Metabolic Disorders

Abstract: Monitoring of patients with inherited metabolic disorders (IMDs) using dried blood spot (DBS) specimens has been routinely used since the inception of newborn screening (NBS) for phenylketonuria in the 1960s. The introduction of flow injection analysis tandem mass spectrometry (FIA–MS/MS) in the 1990s facilitated the expansion of NBS for IMDs. This has led to increased identification of patients who require biochemical monitoring. Monitoring of IMD patients using DBS specimens is widely favoured due to the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 54 publications
0
46
0
3
Order By: Relevance
“…This study made use of dried blood spot sampling, reducing the need for potentially vulnerable people to attend healthcare facilities during the pandemic as well as reduced costs for phlebotomist time and equipment. Dried blood spot sampling has been used since the 1960s for neonatal screening for inborn errors of metabolism [20], and has demonstrated utility across a number of medical uses [21]. Their use as a tool for serological screening of IgG levels is particularly well established [22], and the utility has been highlighted during the COVID-19 pandemic [23].…”
Section: Discussionmentioning
confidence: 99%
“…This study made use of dried blood spot sampling, reducing the need for potentially vulnerable people to attend healthcare facilities during the pandemic as well as reduced costs for phlebotomist time and equipment. Dried blood spot sampling has been used since the 1960s for neonatal screening for inborn errors of metabolism [20], and has demonstrated utility across a number of medical uses [21]. Their use as a tool for serological screening of IgG levels is particularly well established [22], and the utility has been highlighted during the COVID-19 pandemic [23].…”
Section: Discussionmentioning
confidence: 99%
“…DBS specimens for these purposes, especially if self-collected, are advantageous as they would obviate the exposure risk to both the patient and healthcare provider, as well as eliminate the need for phlebotomist time and effort. Notably, DBS analyses have been conducted routinely for newborn screening for nearly six decades and for monitoring of patients with inborn errors of metabolism for at least 25 years ( Guthrie and Susi, 1963 , Moat et al, 2020 , Randell and Lehotay, 1996 ). Other early applications of home-collected DBS for drug monitoring and infectious diseases, such as HIV, have also been successful ( Rattenbury and Tsanakas, 1988 , Spielberg et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of DBS specimens to monitor patients is widely favoured due to the simplicity and convenience of collecting blood from a finger prick onto a filter paper collection device in the patient’s home and mailing the specimen directly to the laboratory for analysis. 5 DBS collection methods have also proven useful for serology testing of hepatitis and human immunodeficiency virus (HIV) in resource-limited settings. 6 8 Furthermore, in a recent cost evaluation study of the use of DBS specimen collection compared to conventional sampling, it was shown that DBS sampling was associated with significant cost reductions.…”
Section: Introductionmentioning
confidence: 99%